Leverage, Sales Growth, and ESG as Determinants of Financial Performance (Moderating Analysis of Board of Commissioners Size in Manufacturing Companies in Indonesia) - Siti Inayah; Tri Neliana (Rescollacom (Research Collaborations Community), 2026)
This study examines the effects of leverage, sales growth, and Environmental, Social, and Governance (ESG) disclosure on the financial performance of manufacturing companies in Indonesia, with board size as a moderating variable. The research is motivated by the need to understand how internal financial and non-financial factors influence firm performance in a dynamic economic environment. A quantitative associative approach is employed using secondary data obtained from annual reports and sustainability reports of consumer goods manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The data are analyzed using panel regression and moderated regression analysis. The results indicate that leverage has a negative and significant effect on financial performance, suggesting that higher debt levels reduce profitability. Sales growth, however, does not have a significant effect, implying that increased revenue does not necessarily translate into improved financial outcomes. In contrast, ESG disclosure shows a positive and significant effect, highlighting the importance of sustainability practices in enhancing firm performance. Furthermore, board size is not found to moderate the relationships between leverage, sales growth, ESG, and financial performance, indicating that the effectiveness of corporate governance depends more on the quality of oversight rather than the number of board members. Overall, this study emphasizes the importance of optimal capital structure and ESG implementation in improving financial performance, while also providing insights into the limited moderating role of board size in the manufacturing sector.